A STUDY ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMK TELKOM PEKANBARU - Azlina Kurniati Kurniati; Eliwarti '; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This descriptive research was conducted to find out the students’ speaking ability in the language function, particularly the expressions of opinion, agreement and disagreement. The samples of this research were 27 students from XI TKJ class of SMK TELKOM Pekanbaru. The researcher used cluster random sampling technique to decide the sample. The instrument used in this research was a Dialogue Completion Task which contained 12 questions. The data were analysed by calculating the students’ score individually and finding out the mean score. The data were presented by using graphic. The data showed that the student’s speaking ability was in good level with the average score 61.38. The result of students’ ability in each aspect was average level for expression of opinion (59.59), while expression of agreement (61.84) and disagreement (60.22) were in good level. Based on the finding, it was suggested that the students need to do more practice in speaking in order to help them to increase their understanding of the materials. The teacher needs to give more opportunities for the students to practice using expression of opinion, agreement and disagreement, especially practice to initiate/ask using of those expressions. Further research can focus on each subtopic in detail, particularly about expression of opinion since it was the students’ lowest score.   Key words: Ability, Speaking, Expression of opinion, agreement and disagreement